2016
DOI: 10.1039/c6ra06688g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spark plasma sintering conditions on the anisotropic thermoelectric properties of bismuth antimony telluride

Abstract: Bismuth antimony telluride (BixSb2-xTe3, 0.4 < x< 0.6) is one of the best and most-used p-type semiconductor materials for near-room-temperature thermoelectric power generation. In this work, p-type Bi0.4Sb1.6Te3 samples were prepared under various conditions (temperature, holding time, and ramp-rate) using spark plasma sintering (SPS). The effects of SPS conditions on the anisotropic thermoelectric properties and microstructure evolutions were systematically investigated. The change of sintering temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…6b inset). These values are comparable with those found in literature for the Bi-Sb-Te system 24 , 25 , 27 , 35 , 39 , 40 . We have calculated the electronic contribution to the thermal conductivity, using a Lorentz number of 1.6 × 10 –8 27 , and found that the lattice contribution at room temperature is about 85.3% in Bi 0.35 Sb 1.65 Te 3 .…”
Section: Resultssupporting
confidence: 91%
“…6b inset). These values are comparable with those found in literature for the Bi-Sb-Te system 24 , 25 , 27 , 35 , 39 , 40 . We have calculated the electronic contribution to the thermal conductivity, using a Lorentz number of 1.6 × 10 –8 27 , and found that the lattice contribution at room temperature is about 85.3% in Bi 0.35 Sb 1.65 Te 3 .…”
Section: Resultssupporting
confidence: 91%
“…More conventional processes, such as hot press and spark plasma sintering, have been also effective in producing Bi2Te3-xSex and BixSb2-xTe3 polycrystalline materials with significant degrees of crystallographic alignment. 13,14 Combining these methodologies with micropowders produced by ball milling, polycrystalline pellets with relatively thick layered structures, ca. 0.5-1 μm, have been obtained.…”
mentioning
confidence: 99%
“…The main reason for this is, of course, the higher thermoelectric performance of BiTe. The ZT value of BiTe is around 1 [22]. ZT values of p-type and n-type polymers are generally clearly below 1 or even below 0.1.…”
Section: Thermoelectric Modulesmentioning
confidence: 93%
“…It was also shown, that in-plane thermal conductivity of these ilms increases with electrical conductivity [21]. For comparison, spark plasma sintered BiTe compounds also show a relatively low thermal conductivity of 0.8 W/(m K) for cross-plane and 1.2 W/(m K) for in-plane measurements [22]. For nanostructured thermoelectric materials, thermal conductivity can be even lower [23].…”
Section: Intrinsically Conductive Polymers For Thermoelectric Applicamentioning
confidence: 95%